Usefulness of hydrographic and sozological databases in ecological studies of rivers in Poland - Graf, Renata; Sobkowiak, Leszek (Ecological Questions, 2012)
An assessment of ecological conditions of streams and other water bodies is one of the requirements of the Water Framework Directive No. 2000/60/EC. The paper deals with the potential use of hydrographic and sozological databases and thematic maps at a scale of 1:50,000 (Hydrographic Map, Sozological Map) compiled on their basis at selected stages of eco-hydrological evaluation of streams, especially at the stage of collecting information on water bodies. Attention was paid to the possible use of that data in identification of sections of river valley estimated from the point of view of its components, i.e. under protection, and determining the level of urbanization of the valley, location of municipal investments, infrastructure and hydraulic structures, which are the measures of the man-made transformation of the valley. An assessment of the ecological state and potential of surface waters is the basis of eco-hydrological studies and the fundamental requirement of the Water Framework Directive, thus is the starting-point for river system valorisation.